HERBICIDE INHIBITORS GLUTAMINE SYNTHETASEI - LATORRE, Debora DE O.; SILVA, Ilca P. DE F. E; JUNIOR, Josué F. DA S.; PUTTI, Fernando F.; SCHIMIDT, Ana P.; LUDWIG, Rafael (Revista Brasileira de Engenharia de Biossistemas, 2013)
Ammonium glufosinate is a post-emergence, non-selective, low translocation and broad-spectrum herbicide of weeds. It is the only herbicide marketed in Brazil with belong to the enzyme glutamine synthetase (GS) inhibitor group. GS is responsible for catalyzing the synthesis of glutamine, incorporating an ammonium molecule in glutamate amino acid, and its inhibition promotes ammonia accumulation to toxic levels in the plants. Liberty Link® plants contain a gene that produces the PAT enzyme, which is responsible for the acetylation of the ammonium glufosinate, inactivating it in plants. In this review, issues regarding persistence in the soil, absorption and translocation, ammonium glufosinate symptons, as well as Liberty Link® technology and resistance cases of weeds will be discussed.